Peran Qanaah dalam Mengatasi Masalah Ekonomi Rumah Tangga - Rahmi Rahmawati; Mulyana Mulyana; Adnan Adnan (Jurnal Riset Agama, 2022)
This research aims to discuss the role of qanaah attitude in dealing with household economic problems based on the perspective of the idrisiyyah order's prosperous family development institution. This research uses qualitative research methods where the resulting source comes from observations and interviews and literature related to research. The results of this study give the understanding that qanaah is a form of gratitude for the efforts that have been made to pick up sustenance. In addition, qanaah is also interpreted as an attitude of acceptance towards all destiny and decrees from Allah Swt., and still accompanied by still trying and trying to get what we need. The Prosperous Family Development Institute is a container in which there are coaching programs as a form of service to pilgrims who want or are married.  LPKS provides guidance on how to become a human being who has good morals and provides tips on how to be a good household. As for the conclusion that can be drawn, the role of qanaah in dealing with economic problems in the household is very important, because with qanaah humans will always feel enough with what they have received so that it will minimize conflicts that occur in the household due to the absence of demands from both sides. This research recommends the importance of understanding and applying qanaah attitudes in family life in order to create a harmonious family.